2014
DOI: 10.1002/pon.3552
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prostate cancer on partners: a qualitative exploration

Abstract: It is clear that prostate cancer impacts substantially on many areas of partner well-being. An effective intervention provided to this population seems warranted and may lead to improvements in partner well-being, assist the couple in lessening the impact of prostate cancer and its treatment on their relationship, and assist in the man's recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 35 publications
(48 reference statements)
1
66
0
Order By: Relevance
“…4,5 ED is associated with significant declines in quality of life and has negative effects on psychological and marital adjustment for both patients 2,6,7 and their partners. 2,[7][8][9][10][11][12] About half of all patients will try a treatment for ED at some point after undergoing prostate cancer treatment. [13][14][15][16] Such ED treatments include phosphodiesterase type 5 inhibitors (PDE5Is), intracavernous injections (ICIs), or vacuum erection devices (VEDs).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 ED is associated with significant declines in quality of life and has negative effects on psychological and marital adjustment for both patients 2,6,7 and their partners. 2,[7][8][9][10][11][12] About half of all patients will try a treatment for ED at some point after undergoing prostate cancer treatment. [13][14][15][16] Such ED treatments include phosphodiesterase type 5 inhibitors (PDE5Is), intracavernous injections (ICIs), or vacuum erection devices (VEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Women play important roles in the overall health of partners diagnosed with prostate cancer and there remain societal and personal expectations for them to play an equally important role in men's nutritional health (Forbat, Place, Hubbard, Leung, & Kelly, 2014;Harden et al, 2002;Wootten et al, 2014). Likewise, women are also expected to play important roles in shaping how men engage in nutrition interventions and diet change after a prostate cancer diagnosis, however, there is little known about how heterosexual couples decide about and make food practice changes in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have shown that prostate cancer diagnosis and treatment side effects can worsen the relationship between patients and their spouses (Ka'opua, Gotay, & Boehm, 2007;Lavery & Clarke, 1999;Navon & Morag, 2003a, 2003bTomaszewski et al, 2017;Wootten et al, 2014). Decreased marital satisfaction is associated with psychological distress and worse quality of life among patients with prostate cancer (Garos, Kluck, & Aronoff, 2007;Pereira, Daibs, Tobias-Machado, & Pompeo, 2011) and their spouses (Garos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%